Parents' Opinion on the Effects of Aquatic Physiotherapy on Delayed Motor Development in Infants - Austėja Klovaitė (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Aquatic therapy is commonly utilized in the rehabilitation of children with developmental disabilities and as a form of physical activity in water for children without developmental disabilities.